Ocular Morbidity Among School Children In Sarojini Nagar Development Block Of Lucknow - Kumar D; Singh J.V; Ahuja P.C; Agarwal J; Mohan U (Wolters Kluwer Medknow Publications, 1992)
A prevalence study was carried out among 430 school children in Sarojini Nagar development block of Lucknow. Age and sex distribution of the study subjects, and different eye diseases including Vitamin A deficiency, refractory error and trachoma have been described.